2019
DOI: 10.18203/2320-1770.ijrcog20196042
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and reliability of ultrasound estimation of fetal weight in women with a singleton term pregnancy

Abstract: Background: Prenatal estimation of birth-weight is of utmost importance to predict the mode of delivery. This is also an important parameter of antenatal care. This study was conducted to evaluate the accuracy of estimated fetal weight by ultrasound, compared with actual birth weight.Methods: This was a prospective and comparative study comprising 110 pregnant women at term. Patients who had their sonography done within 7 days from date of delivery were included. Fetal weight was estimated by Hadlock 2 formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
3
2
0
Order By: Relevance
“…The proportion of fetal weight estimations at our institution that were outside the acceptable 10% variation was similar to previous studies with just over three out of four (75.9%) being within 10% of the recorded birth weight at delivery 1,2,5–8 . A retrospective audit from Wellington Hospital in 2006 also reported an accuracy of 75% 7 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The proportion of fetal weight estimations at our institution that were outside the acceptable 10% variation was similar to previous studies with just over three out of four (75.9%) being within 10% of the recorded birth weight at delivery 1,2,5–8 . A retrospective audit from Wellington Hospital in 2006 also reported an accuracy of 75% 7 .…”
Section: Discussionsupporting
confidence: 88%
“…Other studies prior to 2006 reported fetal weight estimation accuracies that varied between 23 and 78%, 6 but few of these distinguished between overestimated and underestimated group features. More recent studies from other countries have similar degrees of accuracy to ours but they have different population demographics such as lower mean maternal ages, weights and normal range BMI, 5,9 compared with our average BMI of 27kg/m 2 which is classified as overweight.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The overall accuracy of ultrasound in estimating foetal weight at this obstetric ultrasound service was within 15% of birth weight for 92%, and within 10% of birth weight for 77% of scans performed within 7 days of birth. These findings are similar to local and international data 7,12,13 . Accuracy (±15%) was lowest for SGA babies (87%) and highest for AGA babies (93%).…”
Section: Discussionsupporting
confidence: 90%
“…These findings are similar to local and international data. 7,12,13 Accuracy (AE15%) was lowest for SGA babies (87%) and highest for AGA babies (93%). Similarly, sensitivity was lowest for SGA at 51% while adequate for AGA and LGA babies (83% and 82%).…”
Section: Discussionmentioning
confidence: 99%